The adaptor protein 1 medium subunit of plasmodium falciparum - Bezuidenhout, Belinda Catherine (My University, 2014)
Malaria is a tropical disease affecting millions of people worldwide. Plasmodium falciparum is the causative agent of the most severe form of malaria, and therefore insights into the molecular mechanisms by which it functions are critical. The intraerythrocytic stage of the life cycle is responsible for the clinical manifestations of the disease. Numerous proteins are required for the invasion and remodelling of host erythrocytes, and need to be transported to the highly specialized organelles from which they are secreted (invasion proteins), or to the erythrocyte cytoplasm or membrane (exported proteins). It is postulated that newly synthesized proteins are transported from the Golgi network to their target destinations by specific interactions of target sequences of the proteins with the medium subunit (μ) of an adaptor protein (AP1) complex. Bioinformatic analysis of the putative P. falciparum AP1μ subunit, encoded by Pf13_0062, revealed a cargo-binding domain. Three regions, one of which encompassed the putative binding domain, while the other two interrupted this domain, were cloned into the pGEX-4T-2 expression vector. These recombinant proteins were expressed in E. coli with a GST tag, purified and immobilized on glutathione magnetic beads and used to biopan P. falciparum phage display libraries to identify interacting proteins. No binding was observed with the truncated domains, but several specific interactions were identified with the binding domain. One of these peptides was 13 amino acids long and contained a Yxx motif, indicating that PfAP1, like its homologues in higher eukaryotes, binds specifically to this motif in cargo proteins. Other sequences identified included a RRNIFLFINRKKE peptide; exported protein PHISTa; and conserved protein PFL0675c. In the C-terminal region of PFL0675c an armadillo repeat structure was predicted, just downstream of the binding domain identified by biopanning. This region of PFL0675c was therefore cloned into the pET-15b expression vector and expressed as a recombinant His-tagged protein. Slot overlays and far western blotting confirmed the specificity of the interaction with PfAP1. Since PFL0675c does not display the characteristics typical of AP1 cargo, it is postulated to be an accessory protein to the complex. Localization studies performed by transfection V of P. falciparum parasites with pARL2AP1GFP showed that in vivo, PfAP1 localized to distinct foci around the nucleus. Co-localization studies confirmed that PfAP1 localizes to the cis-Golgi in P. falciparum. PfAP1 may therefore be involved in trafficking proteins from the Golgi network to specific subcellular compartments within the parasite. This is the first study identifying interacting partners of PfAP1, and demonstrating its localization in P. falciparum 3D7 parasites.
Keywords: Malaria.; Protozoans.; Plasmodium falciparum.